Penjagaan pesakit strok: adakah ia satu bebanan? apa yang penjaga persepsikan? - Fatimang L,; Rahmah MA, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2011)
Background : This cross-sectional study aimed to investigate the prevalence of the caregiving burden among women who are caregivers to elderly with stroke and factors influencing it. Respondents identified through purposive sampling at the Universiti Malaya Medical Centre from October to December 2007. Methods : Direct methods of data collection (clinical and housing) and indirect (postal) used a structured questionnaire distributed to the guards. Measurements taken include sociodemographic variables of patients and caregivers, the patient, the care, relationships with caregivers and patients with information about stroke. Zarit Burden Interview (ZBI) short version was used to measure the burden of care. Carers' Assessment of Managing Index (Cami) was used to assess coping strategies. A total of 96 respondents took part in this study. Result : The study showed that prevalence of caregiving burden was 35.4%. Burden of care was found to have significant relationships with factors such as marital status, caregivers (p = 0.017), family income (p = 0040) and the patients (p = 0.000). Significant correlation obtained for the coping strategies with the burden (r =- 0228, p 0026). Conclusion : The conclusion shows that policy makers and program managers should appreciate and assist caregivers in performing the role of care. Intervention programs should be designed to suit the needs of the heterogeneous guardian.